Analisis Kualitatif Belanja Pertanian Terhadap Kesejahteraan Petani dan Ekonomi Inklusif Deli Serdang - Rangkuti, Agus Edy; Supriana, Tavi; Lindawati, Lindawati; Ayu, Sri Fajar (CV. Ulil Albab Corp, 2026)
This study examines the impact of government agricultural expenditure on farmers' welfare and inclusive economic growth in Deli Serdang Regency, North Sumatra, using a qualitative approach. The research aims to understand farmers' perceptions of government programs, analyze how implementation mechanisms influence social and economic dynamics, and evaluate their contribution to inclusive growth. Data were collected through in-depth semi-structured interviews with 12 informants, field observations, and document analysis, using thematic analysis for data interpretation. While previous quantitative studies have shown a positive correlation between government support and farmers' welfare, this research reveals a significant gap between policy intentions and on-the-ground reality. Findings indicate that while subsidies provide direct benefits in reducing production costs, aid distribution is often inefficient and poorly targeted due to the role of informal